Подвійні форми - Анікієнко, Л. (Студії мистецтвознавчі, 2008)
The paper deals with the elucidation of one of the interesting and almost undeveloped themes in the special literature. So called “double forms” and their varieties are convincingly enough differentiated; created is proper theoretical systematization of the material as well.